Public sector innovation - Demircioglu, Mehmet Akif; Audretsch, David B. 1954- (Cambridge University Press, 2024)
Governments around the world are under pressure to do more with less. Dispelling the conventional wisdom that government is the enemy of innovation, this book argues that the promise of innovation addressing the most compelling societal problems will only come to fruition if governments become full partners and participants in innovation. The authors provide a systematic overview, analysis, framework, research agenda, and strategic directions for the study of public sector innovation, examining drivers, sources, barriers, typologies, and outcomes of innovation along with ethics. They suggest that innovation in government requires a new approach to public sector strategy, organization, human resources, and culture. Featuring large data analyses and poignant case studies drawn from best practices across the globe, Demircioglu and Audretsch identify what works and what doesn't in transforming governments from the periphery to the very heart of the most profound innovations driving societal change and development
Title from publisher's bibliographic system (viewed on 22 Nov 2024)
Introduction -- What is public sector innovation? -- Public versus private -- The context of public sector innovation -- Innovation typologies -- Why public sector innovation? -- Drivers and conditions for innovation -- Sources of knowledge and collaborative innovation -- Barriers to public sector innovation -- National systems of innovation and market government failure -- Outcomes of public sector innovation -- Ethics and public sector innovation -- Conclusions
Keywords: Public administration; Organizational change; Public policy; Industrial management / Philosophy; Public administration / Economic aspects; Öffentlicher Sektor; Innovation